There is no supporting evidence for a far transfer of general perceptual or cognitive training to sports performance - Fransen, J. (Sports Medicine, 2024)
In this opinion piece I reiterate the concepts of near and far transfer as previously described in the psychological literature. I show that despite very limited evidence, many technologies, tools and methods make questionable claims of eliciting far transfer from generic perceptual and/or cognitive training to sports performance. Specifically, this commentary illustrates with studies on stroboscopic vision, neurofeedback training and executive functions that the claims made for the beneficial effects of these training methods are currently unsubstantiated. I conclude that greater scrutiny by researchers is needed in order to assist practitioners to make better-informed decisions about tools, methods and technologies that may aid sports performance.